Amorphous conjugated coordination polymer aerogel material as well as preparation method and application thereof

By building an amorphous co -cohesion agglomerate, the gel material and ultraviolet irradiation processing, solved the insufficient exposure of the active sites caused by excessive particle size and easy reunion of the co -padda -in -law. The problem realizes the improvement of material performance and the optimization of catalytic reaction dynamics.

CN119371711AActive Publication Date: 2025-01-28JIANGNAN UNIV

Patent Information

Application Number
CN202411529778.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing conjugated coordination polymer materials have a reduced exposure to active sites due to their large particle size and prone to agglomeration, which affects the performance of the material. At the same time, the electrochemical activity of their aerogel materials is low.

Method used

By constructing an amorphous co -cohesion agglomerate material gel material, the co -轭 organic ligand and metal ions are used for matching assembly and induced cross -linking, forming a crystal co -paddling polymerization gel, and processing through ultraviolet irradiation treatment Make the material in non -crystallization and generate unsaturated coated metal activity sites.

Benefits of technology

It improves the diffusion rate of the surface area and reactive molecules of the material in the material, increase the dynamics of catalytic conversion, and enhance electrochemical activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371711A_ABST
    Figure CN119371711A_ABST
Patent Text Reader

Abstract

The invention provides an amorphous conjugated coordination polymer aerogel material as well as a preparation method and application thereof. The method comprises the following steps: firstly, mixing a metal salt solution and a conjugated organic ligand solution, then heating the mixed solution to promote coordination assembly and induced crosslinking to prepare conjugated coordination polymer wet gel, and then drying to obtain crystalline conjugated coordination polymer aerogel; and carrying out ultraviolet radiation treatment on the obtained crystalline conjugated coordination polymer aerogel to finally obtain the amorphous conjugated coordination polymer aerogel. The amorphous conjugated coordination polymer aerogel material prepared by the invention has the advantages of flexible and adjustable molecular structure, unsaturated coordination metal monatomic active sites, high electrochemical activity and the like. In addition, the preparation process is simple and easy to operate, and the obtained amorphous conjugated coordination polymer aerogel material is good in performance and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of amorphous conjugated coordination polymer materials, and in particular relates to an amorphous conjugated coordination polymer aerogel material and a preparation method and application thereof. Background Art

[0002] Conjugated coordination polymers are a new type of single-atom catalytic material with superior electronic conductivity and high stability. This type of material is formed by the effective hybridization of the π orbital of the conjugated organic ligand and the d electron orbital of the transition metal. Its strong conjugation effect and π-d electronic coupling mechanism significantly promote the delocalization of charge, thereby greatly enhancing the conductivity of the material. However, the currently developed conjugated coordination polymer materials face the problems of large particle size and easy agglomeration, which seriously reduces the number of exposed active sites and limits the accessibility of active sites, thereby affecting the overall performance of the material. By constructing a conjugated coordination polymer aerogel material with a nanoporous structure, its specific surface area and the diffusion rate of reactant molecules inside the material can be effectively improved, which improves the above problems to a certain extent. However, the electrochemical activity of the saturated and fully coordinated metal active sites in the currently developed conjugated coordination polymer aerogel materials is still low, which limits its performance improvement in catalytic reactions.

[0003] Compared with traditional crystalline materials, amorphous materials have long-range disorder and contain vacancies / defects. These structural features can effectively improve the adsorption / diffusion behavior of reactants, which is beneficial to improving the catalytic conversion efficiency of reactant molecules / ions. Therefore, it is of great significance to realize the preparation of amorphous conjugated coordination polymer aerogel materials, which can improve the problem of easy stacking and agglomeration of currently developed conjugated coordination polymer materials, and can also improve the problem of poor electrochemical activity of currently developed conjugated coordination polymer aerogel materials, thereby achieving performance improvement and application expansion. Summary of the invention

[0004] Purpose of the invention: In view of the problems and shortcomings of the prior art, the present invention provides an amorphous conjugated coordination polymer aerogel material and a preparation method and application thereof. The prepared amorphous conjugated coordination polymer aerogel material contains unsaturated coordinated metal single atom active sites, which helps to solve the problem of low catalytic activity of existing crystalline conjugated coordination polymer aerogel materials. In addition, the amorphous conjugated coordination polymer aerogel material has the characteristics of long-range disorder, which can effectively improve the adsorption / diffusion behavior of reactants and help improve the kinetics of catalytic conversion.

[0005] The first aspect of the present invention is to provide an amorphous conjugated coordination polymer aerogel material, which is constructed from metal single atoms and conjugated organic ligands; the metal single atoms include at least one of nickel, copper, zinc, aluminum, bismuth, and cobalt, and the conjugated organic ligands include at least one of 2,3,6,7,10,11-hexahydroxytriphenyl, hexahydroxybenzene, 2,3,6,7,10,11-hexaaminotriphenyl, and hexaaminobenzene; the amorphous conjugated coordination polymer aerogel material is an amorphous material and contains unsaturated coordinated metal active sites.

[0006] The second aspect of the present invention is to provide a method for preparing an amorphous conjugated coordination polymer aerogel material, the method comprising the following steps:

[0007] (1) mixing a metal salt solution with a conjugated organic ligand solution, and then heating the mixed solution to promote coordination assembly and induce cross-linking to prepare a conjugated coordination polymer wet gel, and then drying to obtain a crystalline conjugated coordination polymer aerogel material;

[0008] (2) The obtained crystalline conjugated coordination polymer aerogel material is subjected to ultraviolet irradiation treatment to prepare an amorphous conjugated coordination polymer aerogel material.

[0009] In one implementation case, the molar ratio of the metal salt to the conjugated organic ligand in step (1) is 1 to 2:1, preferably 1.5:1.

[0010] In one embodiment, the conjugated organic ligand in step (1) is one of 2,3,6,7,10,11-hexahydroxytriphenyl, hexahydroxybenzene, 2,3,6,7,10,11-hexaaminotriphenyl, and hexaaminobenzene, preferably 2,3,6,7,10,11-hexahydroxytriphenyl.

[0011] In one implementation case, the solvent in step (1) is one of water, dimethyl sulfoxide, acetone, and N,N-dimethylformamide, preferably dimethyl sulfoxide.

[0012] In one implementation case, the metal salt in step (1) is one of acetate, chloride, sulfate, and nitrate, preferably acetate.

[0013] In one embodiment, the heating treatment temperature in step (1) is 65-80°C, preferably 75°C.

[0014] In one embodiment, the concentration of the conjugated organic ligand solution in step (1) is 0.4 to 0.6 mol·L -1 , preferably 0.5 mol·L -1 .

[0015] In one embodiment, the concentration of the metal salt solution in step (1) is 0.3-1.2 mol·L -1 .

[0016] Furthermore, in one embodiment, the concentration of the metal salt solution in step (1) is 0.5-1.0 mol·L -1 , more preferably 0.75 mol·L -1 .

[0017] In one implementation case, the heating treatment time in step (1) is 24 to 48 hours, preferably 24 hours.

[0018] In one implementation case, the drying treatment in step (1) includes at least one of atmospheric pressure drying, freeze drying, and supercritical drying, preferably supercritical drying; the treatment time is 8 to 12 hours, preferably 12 hours.

[0019] In one implementation case, the ultraviolet irradiation treatment time in step (2) is 1 to 6 hours, preferably 3 hours.

[0020] In one implementation case, the wavelength range of the ultraviolet light for ultraviolet irradiation treatment in step (2) is 10 nm to 380 nm.

[0021] Furthermore, in one implementation case, the wavelength of ultraviolet light in the ultraviolet irradiation treatment in step (2) is 365 nm.

[0022] On the other hand, the present invention provides an amorphous conjugated coordination polymer aerogel material prepared by the above method.

[0023] The inventive principle of the present invention is: conjugated organic ligands and metal ions are coordinated and assembled and induced to crosslink to form a crystalline conjugated coordination polymer aerogel; the subsequent ultraviolet irradiation treatment causes some coordination bonds in the crystalline conjugated coordination polymer aerogel to break, thereby generating unsaturated coordination metal active sites, and also causing the material to be amorphous, thereby obtaining an amorphous conjugated coordination polymer aerogel material. The ultraviolet irradiation treatment does not destroy the nanoporous structural characteristics of the amorphous conjugated coordination polymer aerogel material.

[0024] On the other hand, the present invention also provides an application of the above-mentioned preparation method or an application of an amorphous conjugated coordination polymer aerogel material, including applications in catalysis, electrochemical energy storage, electromagnetic wave shielding and absorption, sensors and electronic devices and other fields.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The amorphous conjugated coordination polymer aerogel material prepared by the present invention has the advantages of flexible and adjustable molecular structure, containing unsaturated coordinated metal single atom active sites, and high electrochemical activity.

[0027] 2. The amorphous conjugated coordination polymer aerogel material prepared by the present invention has the characteristics of long-range disorder, which can effectively improve the adsorption / diffusion of reactants and enhance the kinetics of catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The schematic diagrams for comparing the structures of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 are shown.

[0029] Figure 2 These are scanning electron microscope photos of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1.

[0030] Figure 3 These are transmission electron microscope photos of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1; the illustration in the upper left corner is a crystal diffraction photo of the amorphous conjugated coordination polymer aerogel material and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1.

[0031] Figure 4 The X-ray diffraction patterns of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 are shown.

[0032] Figure 5 The electron paramagnetic resonance spectra of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 are shown.

[0033] Figure 6 These are the test results of linear sweep voltammetry curves of the amorphous conjugated coordination polymer aerogel material of Example 1, the crystalline conjugated coordination polymer aerogel material of Comparative Example 1, and the amorphous conjugated coordination polymer material of Comparative Example 2.

[0034] Figure 7 These are the in-situ electrochemical impedance spectroscopy test results of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1. DETAILED DESCRIPTION

[0035] The present invention provides an amorphous conjugated coordination polymer aerogel material and a preparation method and application thereof. First, a metal salt solution and a conjugated organic ligand solution are mixed, and the mixed solution is heated to promote coordination assembly and induced cross-linking, followed by drying to obtain a crystalline conjugated coordination polymer aerogel material, and finally ultraviolet irradiation treatment to obtain an amorphous conjugated coordination polymer aerogel material. The amorphous conjugated coordination polymer aerogel material prepared by the present invention has the advantages of flexible and adjustable molecular structure, containing unsaturated coordinated single atom active sites, and high electrochemical activity. The preparation process is simple and easy to operate, and the obtained amorphous conjugated coordination polymer aerogel material has excellent performance and good application prospects.

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Unless otherwise specified, the sources of the reagents used in the embodiments of the present invention can be purchased from the market.

[0038] The present invention provides a characterization test result diagram of Example 1, and other embodiments all adopt the same characterization test method. Those skilled in the art can directly and unambiguously determine the content of the embodiments of the present invention through the characterization test method provided by the present invention.

[0039] Example 1: Preparation of amorphous conjugated coordination polymer aerogel material

[0040] (1) Using a balance, 187 mg (0.75 mmol) of nickel acetate tetrahydrate was weighed and dissolved in 1.0 mL of deionized water; 162 mg (0.50 mmol) of 2,3,6,7,10,11-hexahydroxytriphenyl was weighed and dissolved in 1.0 mL of dimethyl sulfoxide; the mixture was ultrasonically dispersed for 1 h; after being fully dissolved, the mixture was mixed in a glass bottle and placed in a 75°C forced air oven for 24 h to obtain a conjugated coordination polymer wet gel; and then a crystalline conjugated coordination polymer aerogel material was obtained by supercritical drying.

[0041] (2) The obtained crystalline conjugated coordination polymer aerogel material is subjected to 365 nm wavelength ultraviolet irradiation treatment for 3 h to obtain an amorphous conjugated coordination polymer aerogel material.

[0042] Example 2: Preparation of amorphous conjugated coordination polymer aerogel material

[0043] (1) Using a balance, 322 mg (1.3 mmol) of nickel acetate tetrahydrate was weighed and dissolved in 1.2 mL of deionized water; 150 mg (0.86 mmol) of hexahydroxybenzene was weighed and dissolved in 1.2 mL of dimethyl sulfoxide; the mixture was ultrasonically dispersed for 1 h; after being fully dissolved, the mixture was mixed in a glass bottle and placed in a 75°C forced air oven for 24 h to obtain a conjugated coordination polymer wet gel; and then a crystalline conjugated coordination polymer aerogel material was obtained by supercritical drying.

[0044] (2) The obtained crystalline conjugated coordination polymer aerogel material is subjected to 365 nm wavelength ultraviolet irradiation treatment for 3 h to obtain an amorphous conjugated coordination polymer aerogel material.

[0045] Comparative Example 1: Preparation of crystalline conjugated coordination polymer aerogel material

[0046] The difference between this comparative example and Example 1 is that only a crystalline conjugated coordination polymer aerogel material is prepared without ultraviolet irradiation treatment, and the comparative example includes the following steps:

[0047] (1) Using a balance, 187 mg (0.75 mmol) of nickel acetate tetrahydrate was weighed and dissolved in 1.0 mL of deionized water; 162 mg (0.50 mmol) of 2,3,6,7,10,11-hexahydroxytriphenyl was weighed and dissolved in 1.0 mL of dimethyl sulfoxide; the mixture was ultrasonically dispersed for 1 h; after being fully dissolved, the mixture was mixed in a glass bottle and placed in a 75°C forced air oven for 24 h to obtain a conjugated coordination polymer wet gel; and then a crystalline conjugated coordination polymer aerogel material was obtained by supercritical drying.

[0048] Comparative Example 2: Preparation of amorphous conjugated coordination polymer materials

[0049] The difference between this comparative example and Example 1 is that only an amorphous conjugated coordination polymer material is prepared, which includes the following steps:

[0050] (1) Using a balance, 39.8 mg (0.16 mmol) of nickel acetate tetrahydrate was weighed and dissolved in 2.0 mL of deionized water. 26 mg (0.08 mmol) of 2,3,6,7,10,11-hexahydroxytriphenyl was weighed and dissolved in 2.0 mL of dimethyl sulfoxide. The mixture was ultrasonically dispersed for 1 h. After being fully dissolved, the mixture was mixed in a glass bottle and placed in a 75° C. forced air oven for 24 h to obtain a precipitate. The precipitate was then dried at normal pressure to obtain an amorphous conjugated coordination polymer material.

[0051] (2) The obtained crystalline conjugated coordination polymer material was subjected to ultraviolet irradiation treatment at a wavelength of 365 nm for 3 h to obtain an amorphous conjugated coordination polymer material without forming a gel.

[0052] Test example: Performance test of amorphous conjugated coordination polymer aerogel materials

[0053] like Figure 1 The schematic diagrams of the structures of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 are compared. Ultraviolet irradiation treatment can break some coordination bonds in the crystalline conjugated coordination polymer aerogel, thereby generating unsaturated coordinated metal active sites and causing the material to become amorphous, thereby obtaining an amorphous conjugated coordination polymer aerogel material.

[0054] Table 1 shows the inductively coupled plasma emission spectroscopy test results of the nickel-based amorphous conjugated coordination polymer aerogel material. In the amorphous conjugated coordination polymer aerogel material obtained in Example 1, the content of metal Ni is higher than 15 wt.%.

[0055] Table 1. Inductively coupled plasma emission spectroscopy test results of nickel-based amorphous conjugated coordination polymer aerogel materials

[0056]

[0057] like Figure 2 a, b show scanning electron microscope photos of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1. It can be observed that the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 both have obvious porous morphology of aerogel, which fully demonstrates that the ultraviolet irradiation treatment has no effect on the morphology of the aerogel material.

[0058] like Figure 3 a, b show transmission electron microscope photos of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1. It can be observed that Figure 3 The amorphous conjugated coordination polymer aerogel material in Example 1 in a has no lattice fringes, while Figure 3 The crystallized conjugated coordination polymer aerogel material of comparative example 1 in b has obvious 1.8 nm lattice fringes, which fully confirms the crystallization of comparative example 1. In addition, the crystal diffraction photograph in the upper left corner shows that the amorphous conjugated coordination polymer aerogel material of example 1 has no crystal diffraction rings, while the crystallized conjugated coordination polymer aerogel material of comparative example 1 has obvious crystal diffraction rings.

[0059] like Figure 4The figure shows the X-ray diffraction patterns of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1. The XRD pattern of the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 has peaks at 2θ=4.7°, 9.3°, 14.1°, 16.3° and 27.1°, which correspond to the (010), (020), (030), (220) and (002) crystal planes, respectively, while the amorphous conjugated coordination polymer aerogel material of Example 1 does not have any characteristic peaks at these crystal planes, which also confirms that Figure 3 Results from transmission electron microscopy and crystal diffraction.

[0060] like Figure 5 The electron paramagnetic resonance spectra of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 are shown. Figure 5 It can be clearly seen that the amorphous conjugated coordination polymer aerogel material of Example 1 has more unpaired electrons than the crystalline conjugated coordination polymer aerogel material of Comparative Example 1, confirming that it contains unsaturated coordinated metal single atom active sites.

[0061] like Figure 6 The linear sweep voltammetry curves of the amorphous conjugated coordination polymer aerogel material of Example 1, the crystalline conjugated coordination polymer aerogel material of Comparative Example 1, and the amorphous conjugated coordination polymer material of Comparative Example 2 in a CO2-saturated 0.5M KHCO3 aqueous solution (neutral electrolyte system) are shown. The results show that: the amorphous conjugated coordination polymer aerogel material of Example 1 has a linear sweep voltammetry curve of 10 mA cm -2 The overpotential at 10 mA cm -2 The overpotential is 543 mV. The amorphous conjugated coordination polymer material of Comparative Example 2 has an overpotential of 10 mA cm -2 The overpotential at 200 ℃ is 665 mV. The above results show that the electrocatalytic oxygen evolution performance of the amorphous conjugated coordination polymer aerogel material in Example 1 in a neutral electrolyte system is better than that of the crystalline conjugated coordination polymer aerogel material in Comparative Example 1 and the amorphous conjugated coordination polymer material in Comparative Example 2. The excellent performance of the amorphous conjugated coordination polymer aerogel material prepared by the present invention is attributed to its combination of amorphous characteristics and aerogel porous structure characteristics.

[0062] like Figure 7 The results are shown as in-situ electrochemical impedance spectroscopy test results of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 in a CO2-saturated 0.5M KHCO3 aqueous solution. Figure 7 It can be seen that compared with the crystalline conjugated coordination polymer aerogel material in comparative example 1, the amorphous conjugated coordination polymer aerogel material in example 1 is smaller. Figure 7The adsorption capacitance value shown in b also shows that the reactants adsorbed on the surface of the amorphous conjugated coordination polymer aerogel material in Example 1 are more than those adsorbed on the surface of the crystalline conjugated coordination polymer aerogel material in Comparative Example 1. The above results all confirm that the amorphous conjugated coordination polymer aerogel material can effectively improve the adsorption / diffusion of reactants, thereby achieving an improvement in the kinetics of the catalytic reaction. This is consistent with Figure 6 The catalytic performance comparison results of the amorphous conjugated coordination polymer aerogel material of Example 1 and the crystalline conjugated coordination polymer aerogel material of Comparative Example 1 are confirmed.

[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. An amorphous conjugated coordination polymer aerogel material, characterized in that: The amorphous conjugated coordination polymer aerogel material is constructed by metal single atoms and conjugated organic ligands; the metal single atoms include at least one of nickel, copper, zinc, aluminum, bismuth, and cobalt, and the conjugated organic ligands include at least one of 2,3,6,7,10,11-hexahydroxytriphenyl, hexahydroxybenzene, 2,3,6,7,10,11-hexaaminotriphenyl, and hexaaminobenzene; The amorphous conjugated coordination polymer aerogel material is an amorphous material and contains unsaturated coordinated metal active sites.

2. The amorphous conjugated coordination polymer aerogel material according to claim 1, characterized in that: The amorphous conjugated coordination polymer aerogel material has a high conductivity at 10 mA cm -2 The overpotential at the current density is less than 300mV, and / or Preferably, the amorphous conjugated coordination polymer aerogel material has a -2 The overpotential at the current density is lower than 250 mV, more preferably 200-250 mV.

3. A method for preparing an amorphous conjugated coordination polymer aerogel material, characterized in that: The following steps are involved: (1) mixing a metal salt solution with a conjugated organic ligand solution, and then heating the mixed solution to promote coordination assembly and induce cross-linking to prepare a conjugated coordination polymer wet gel, and then drying to obtain a crystalline conjugated coordination polymer aerogel material; (2) The obtained crystalline conjugated coordination polymer aerogel material is subjected to ultraviolet irradiation treatment to obtain an amorphous conjugated coordination polymer aerogel material.

4. The method according to claim 3, characterized in that The metal type of the metal salt in step (1) includes at least one of nickel, copper, zinc, aluminum, bismuth and cobalt; and / or Preferably, the metal salt in step (1) comprises at least one of acetate, chloride, sulfate and nitrate; and / or The conjugated organic ligand in step (1) is at least one of 2,3,6,7,10,11-hexahydroxytriphenyl, hexahydroxybenzene, 2,3,6,7,10,11-hexaaminotriphenyl, and hexaaminobenzene; and / or The solvent in step (1) is at least one of water, dimethyl sulfoxide, acetone, N,N-dimethylformamide, etc.

5. The method according to claim 3, characterized in that: In the step (1), the molar ratio of the metal salt to the conjugated organic ligand is 1 to 2:1, preferably 1.5:

1.

6. The method according to claim 3 or 5, characterized in that: The concentration of the metal salt solution in step (1) is 0.3 to 1.2 mol·L -1 , and / or Preferably, the concentration of the metal salt solution in step (1) is 0.5-1.0 mol·L -1 , more preferably 0.75 mol·L -1 , and / or Preferably, the concentration of the conjugated organic ligand solution in step (1) is 0.2 to 0.8 mol·L -1 Preferably, the concentration of the conjugated organic ligand solution is 0.4 to 0.6 mol·L -1 , more preferably 0.5 mol·L -1 .

7. The method according to claim 3, characterized in that In the step (1), the heating treatment temperature is 65 to 80° C., and the reaction time is 24 to 48 hours.

8. The method according to claim 3, characterized in that The drying process in step (1) includes at least one of atmospheric pressure drying, freeze drying, and supercritical drying.

9. The method according to claim 3, characterized in that: In the step (2), the ultraviolet irradiation treatment is performed for 1 to 6 hours, and the wavelength range of the ultraviolet light is 10 nm to 380 nm.

10. Use of the amorphous conjugated coordination polymer aerogel material as claimed in any one of claims 1 to 2 or any one of claims 3 to 9, including application in the fields of catalysis, adsorption, sensing, electrochemical energy storage, electromagnetic shielding or wave absorption.

Citation Information

Patent Citations

  • Amorphous metal-organic frameworks

    CN107771084A

  • Preparation method and application of in-situ hydrazide three-dimensional MOFs material

    CN113817174A

  • Amorphous MOF nano photosensitizer as well as preparation method and application thereof

    CN114790218A

  • Mn-MOF material and application thereof in ozone degradation in mobile phase system

    CN114950568A

  • Conjugated coordination polymer aerogel material as well as preparation method and application thereof

    CN117866274A

Cited By

  • High-entropy conjugated coordination polymer aerogel material as well as preparation method and application thereof

    CN121293519A